Edmodo and Chamilo Media in Know-Want-Learned Strategy to Teach Reading Comprehension of Recount Texts to Students with Different Reading Habits - Rahmah, Siti Nafakhati; Saleh, Mursid; Anggani Linggar Bharati, Dwi (Universitas Negeri Semarang, 2020)
This research is based on the phenomena that the students often find difficulties in comprehending English texts, especially in recount texts. This research aims at investigating the effectiveness of Edmodo and Chamilo media in Know-Want-Learned strategy to teach reading comprehension of recount texts to students with good and poor reading habits. An experimental research with 2x2 factorial design was applied in this study. The samples of this research were the students of X TKJ 1 and X TKJ 2 of SMKN 1 Sragi Pekalongan. Observation, questionnaires, and tests were the instruments of the research. T-test and ANOVA were the data analysing methods. The research findings revealed that firstly Edmodo media in Know-Want-Learned (KWL) strategy was effective to teach reading comprehension of recount texts to students with good and poor reading habits. Secondly, Chamilo media in Know-Want-Learned (KWL) strategy was also effective to teach reading comprehension of recount texts to students with good and poor reading habits. Thirdly, there was no significant difference on the effect of Edmodo and Chamilo media to teach reading comprehension of recount texts to students with good reading habit. On the contrary, there was significant difference on the effect of Edmodo and Chamilo media to teach reading comprehension of recount texts to students with poor reading habit. Finally, there was no effective interaction among Edmodo and Chamilo media, reading strategy, students’ reading habits, and students’ reading comprehension of recount texts.